Attitudes of Manufacturers, Law Enforcing Officers and Consumers on the Sri Lankan Labelling Regulations: A Qualitative study - Charith Amidha Hettiarachchi; Sumal Nandasena; Mahendra Arnold (College of Community Physicians of Sri Lanka, 2021)
Introduction: Food label is the main medium of communication between manufacturer, distributor and consumer. It is regulated via law enforcing officers.   Objectives: To identify the attitudes of manufacturers /distributors, law enforcing officers and consumers towards the Sri Lankan labelling regulation, its implementation and practical difficulties   Methods: A qualitative study conducted through focus group discussions (FGD); two FGDs for 14 manufacturers/distributors, three for 23 law enforcing officers and another two for 19 consumers. Participants were selected by convenience sampling. A semi-structured guide was used to collect data. Ideas generated were thematically analysed.   Results: Manufacturers/distributors perceived labelling regulations as useful. The colour code for sugar level and the expiry date were the main interests of consumers. Consumers believed that the labels do not always provide correct information. Consumers were not satisfied on the implementation of labelling regulations, location of the label and the expiry date. Law enforcing officers admitted that they give minimum priority to labelling regulations due to inadequate knowledge, competence and legal support. They further expressed uncertainty on authority over Ayurveda foods.   Conclusions & Recommendations: Consumers and law enforcing officers were of the opinion that labelling regulations are poorly implemented. The legal definition of 'food' has failed to exclude or include Ayurveda food precisely, therefore explicit exclusion is necessary. Both manufacturers / distributors and law enforcing officers need to be provided with training on regulations as they admitted that their existing knowledge and competency are poor.